Outcomes of coronavirus 2019 infection in patients with chronic kidney disease: a systematic review and meta-analysis - Yi-Chih Lin; Tai-Shuan Lai; Shuei-Liong Lin; Yung-Ming Chen; Tzong-Shinn Chu; Yu-Kang Tu (SAGE Publishing, 2021)
Background: Information on coronavirus disease 2019 (COVID-19) infection in patients with chronic kidney disease (CKD) remains limited. To understand the influence of COVID-19 infection in patients with pre-existing CKD, we conducted a systematic review and meta-analysis to evaluate and compare the risks of all-cause mortality, hospitalization, and critical progression between patients with and without CKD. Methods: We selected randomized controlled trials (RCTs), prospective or retrospective observational, case-control, cross-sectional, and case-series studies analyzing outcomes of COVID-19 infection in patients with pre-existing CKD from the PubMed, Embase, and Cochrane Central Register of Controlled Trials databases published on the Internet before 16 July 2020. Results: A total of 27 studies comprising 77,856 patients with COVID-19 infection was identified; 3922 patients with pre-existing CKD were assigned CKD group, and 73,934 patients were assigned to the non-CKD group. The pooled analysis showed that patients with CKD had a significantly higher risk of all-cause mortality and hospitalization than those without CKD [odds ratio (OR) 2.25, 95% confidence interval (CI) 1.91-2.66, p  < 0.001; OR 4.29, 95% CI 2.93-6.28, p  < 0.001; respectively]. Patients with CKD had a higher risk of critically ill conditions than those without CKD in the pooled analysis of studies with multivariable adjustment (adjusted OR 2.12, 95% CI 0.95-4.77, p  = 0.07) and in the analysis of all included studies (OR 1.27, 95% CI 0.71-2.26, p  = 0.41), but both analyses did not attain statistical significance. Conclusion: COVID-19 infected patients with CKD had significantly increased risks of all-cause mortality and hospitalization compared with those without CKD.